MODERN TECHNOLOGIES FOR DEVELOPING CREATIVE THINKING OF STUDENTS - Maftuna Abdumajitova (Euro Asian Journal Publishing, 2023)
In this article was talk about modern technologies for the development of students' creative thinking
Keywords: creative thinking; brainstorming; digital technology; flexibility